Maximus I. von Turin : die Verkündigung eines Bischofs der frühen Reichskirche im zeitgeschichtlichen, gesellschaftlichen und liturgischen Kontext - Merkt, Andreas. (Vigiliae Christianae, Supplements, 1997)
This volume deals with the sermons of St. Maximus I, Bishop of Turin about AD 305-420. It presents an exemplary study which, besides clarifying problems of dating and authorship, points out the importance of context for an appropriate interpretation of sermon literature. The sermons are thus placed in the contexts of contemporary history, of society and of liturgy. The liturgical contextualisation forms the core of the book. The author reconstructs the liturgical year of late-Antique Turin and takes it as the basis of a detailed diachronic analysis of the bishop's preaching from advent to pentecost. Additionally, the Feasts of the Saints are seen in their kerygmatic function. In a concluding chapter the author tackles such problems as the exegetical nature of preaching and the importance of the Bible.